2017
DOI: 10.1038/s41598-017-00663-1
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of hormone receptor status and distant recurrence-free interval on survival benefits from trastuzumab in HER2-positive metastatic breast cancer

Abstract: We sought to investigate the impact of hormone receptor (HR) status and distant recurrence-free interval (DRFI) on the degree of overall survival (OS) benefit from palliative trastuzumab-containing treatment in HER2-positive metastatic breast cancer (MBC). Here, we retrospectively identified 588 eligible HER2-positive patients with postoperative distant recurrence. DRFI of HR+HER2+ MBC patients (median: 30.7 months, IQR: 18.5–45.9, P < 0.001) was significant longer compared with HR−HER2+ patients. Patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…CTGF also regulates KLF4 to trigger EMT in Kawasaki disease 30 . CTGF enhances ANGPT2 expression, a key element in tumor angiogenesis 31 . The suppression of CTGF expression appreciably decreases angiogenesis 31 and tumor growth 32 in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…CTGF also regulates KLF4 to trigger EMT in Kawasaki disease 30 . CTGF enhances ANGPT2 expression, a key element in tumor angiogenesis 31 . The suppression of CTGF expression appreciably decreases angiogenesis 31 and tumor growth 32 in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…CTGF has also been reported to promote EMT process in Kawasaki disease by regulation of KLF4 [ 15 ]. In the process of angiogenesis, CTGF has been demonstrated to be the regulator of ANGPT2 expression, which is key factor for tumor angiogenesis [ 37 ]. Silencing CTGF expression significantly reduced tumor growth [ 7 ] and angiogenesis [ 37 ] in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of angiogenesis, CTGF has been demonstrated to be the regulator of ANGPT2 expression, which is key factor for tumor angiogenesis [ 37 ]. Silencing CTGF expression significantly reduced tumor growth [ 7 ] and angiogenesis [ 37 ] in vivo. In this present study, CTGF was for the first time identified as the direct target of miR-218 by dual luciferase assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 With a larger sample size, our analysis shows the important prognostic role In addition, our results provide further evidence on the different behaviour of HER2-positive tumours according to hormone receptor status. [13][14][15][16][17][18] As compared to patients with hormone receptor-positive disease, those with hormone receptor-negative tumours had higher likelihood to relapse within 12 months following completion of adjuvant trastuzumab and had poorer OS irrespective of TFI. These data further highlight the need to pursue in research efforts aiming to improve the outcomes of patients with metastatic HER2-positive disease with different approaches according to hormone receptor status.…”
Section: Discussionmentioning
confidence: 99%